PROSES PEMBENTUKAN DATA ARKEOLOGI PADA KAPAL KARAM PULAU NUSA, KEPULAUAN BAWEAN - Mochammad Fauzi Hendrawan (Berkala Arkeologi Sangkhakala, 2019)
Indonesian archipelago holds considerably amount of archaeological data includes shipwreck that vary from various periods and types. In Bawean Island, a shipwreck with steamer component indicated from the 19th century named Pulau Nusa was found. In 2016, Pulau Nusa shipwreck was found by Balai Arkeologi Yogyakarta in a fragmentary shape with scattered components. Numbers of scattered components has concreted with coral and the bottom part has gone through sedimentation thus buried in sea floor. This research focused on the underlying process behind the current condition of Pulau Nusa shipwreck. Conducted as an explorative research with inductive reasoning, this research used two main method of analysis, i.e environmental and contextual analysis. These two method of analysis are used to answer the data formation process which divided into two steps, behavioral process (pre-depositional) and transformation process (depositional and post-depositional) along with cultural and noncultural factors that have impact on those process. From the synthesis of two analyses came the conclusion at first the formation of archaeological data influenced by Noncultural transform, but further because it is located in the shallow sea and the existence of human activity due to the economic value of the environment and shipwreck itself, the cultural transformation factor also contributes to the role.